The HIV-1 Vpu viroporin inhibitor BIT225 does not affect Vpu-mediated tetherin antagonism. - Björn D Kuhl (Public Library of Science (PLoS), 2011)
Among its many roles, the HIV-1 accessory protein Vpu performs a viroporin function and also antagonizes the host cell restriction factor tetherin through its transmembrane domain. BIT225 is a small molecule inhibitor that specifically targets the Vpu viroporin function, which, in macrophages, resulted in late stage inhibition of virus release and decreased infectivity of released virus, a phenotype similar to tetherin-mediated restriction. Here, we investigated whether BIT225 might mediate its antiviral function, at least in part, via inhibition of Vpu-mediated tetherin antagonism. Using T-cell lines inducible for tetherin expression, we found that BIT225 does not exert its antiviral function by inhibiting Vpu-mediated tetherin downmodulation from the cell surface, the main site of action of tetherin activity. In addition, results from a bioluminescence resonance energy transfer (BRET) assay showed that the Vpu-tetherin interaction was not affected by BIT225. Our data provide support for the concept that tetherin antagonism and viroporin function are separable on the Vpu transmembrane and that viroporin function might be cell-type dependent. Further, this work contributes to the characterization of BIT225 as an inhibitor that specifically targets the viroporin function of Vpu.